GE14 soon after CNY? - Amar, Syah Mohsen (The Sun, 2017)
BAGAN DATUK: Deputy Prime Minister Datuk Seri Ahmad Zahid Hamidi has given a hint the 14th general election (GE14) will likely be held soon after Chinese New Year.